Dampak fasilitas dan pelayanan perpustakaan terhadap minat membaca mahasiswa IAIN Ponorogo - mujiati Mujiati (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2022)
Library facilities and services are very important in attracting interest in reading library visitors. This research aims to determine the extent to which both have an impact on users. The study used two methods, namely quantitative and qualitative. Collecting data by distributing questionnaires to 30 people and interviewing three people who became informants. Both methods are used to reinforce the existing data. The qualitative data analysis technique uses the Miles and Huberman method. The conclusion of this study is that the facilities that need to be improved are the addition of laptop and computer plugs. In general, the service is in the good category.